Illustrated history of landscape design - Boults, Elizabeth; Sullivan, Chip. (New Jersey : John Wiley & Son, Inc., 2010)
Illustrated History of Landscape Design takes an optical sweep of the iconic landscapes constructed throughout the ages. Organized by century and geographic region, this highly visual reference uses hundreds of masterful pen-and-ink drawings to show how historical context and cultural connections can illuminate today's design possibilities. This guide includes: Storyboards, case studies, and visual narratives to portray spaces; Plan, section, and elevation drawings of key spaces; Summaries of design concepts, principles, and vocabularies; Historic and contemporary works of art that illuminate a specific era; and Descriptions of how the landscape has been shaped over time in response to human need." "Directing both students and practitioners along a visually stimulating timeline, Illustrated History of Landscape Design is a valuable educational tool as well as an endless source of inspiration.
Prehistory-6th century. Cosmological landscapes -- Ancient gardens -- Landscape and architecture -- Genius loci -- 6th-15th centuries. Western Europe : walled minds, walled gardens -- Moorish Spain : an indelible influence -- China : nature's splendor in a garden -- Japan : in the spirit of nature -- 15th century. Japan : Muromachi era -- China : Ming dynasty -- Central Asia : Timurid garden cities -- Italy : curious minds, broadened vistas -- 16th century. Italy : the rebirth of Rome -- Renaissance gardens in France and England -- The early botanic garden : an encyclopedia of plants -- Early Mughal gardens : Persian art forms travel east -- Japan : the Momoyama era -- 17th century. Japan : Edo period -- The Mughal empire : sacred symmetries -- Persian gardens of paradise -- Italian Baroque styles -- The flowering of the Dutch landscape -- English gardens : a restrained mix of European styles -- French classical gardens: the control of nature -- 18th century. England : the development of the landscape garden -- The landscape garden in France -- China : Qianlong's imprint -- Early American gardens : homeland traditions -- 19th century. England : the Victorians and their plants -- France : republics and empires -- Landscape architecture in America -- 20th century. The Gilded Age : extremes of wealth and poverty -- The new aesthetic of modernism -- Environmental art: nature as medium -- Artistic trends in landscape design -- Environmental and ecological design -- Postmodern landscapes -- 21st century. A sustainable Earth : ten ideas. Endnotes -- Bibliography -- Index.
Includes bibliographical references and index.
Keywords: LANDSCAPE DESIGN